2016
DOI: 10.1371/journal.pone.0147764
|View full text |Cite
|
Sign up to set email alerts
|

FoxC2 Enhances BMP7-Mediated Anabolism in Nucleus Pulposus Cells of the Intervertebral Disc

Abstract: Bone-morphogenetic protein-7 (BMP-7) is a growth factor that plays a major role in mediating anabolism and anti-catabolism of the intervertebral disc matrix and cell homeostasis. In osteoblasts, Forkhead box protein C2 (FoxC2) is a downstream target of BMPs and promotes cell proliferation and differentiation. However, the role FoxC2 may play in degenerative human intervertebral disc tissue and the relationship between FoxC2 and BMP-7 in nucleus pulposus (NP) cells remain to be elucidated. This study aims to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…In myoblasts, decreased endogenous Foxc2 reduced cell proliferation activity, while increased expression of Foxc2 promoted cell proliferation [ 13 ]. In osteoblasts, upregulated Foxc2 facilitates cell proliferation in vitro [ 32 ], and Foxc2 might encourage the survival and proliferation of osteoblasts by upregulating integrin β 1 [ 11 ]. Consistent with the previous reports [ 13 , 32 ], our data showed that the proliferation of Foxc2 gene-transfected SCAP was slightly stronger than that of the other three groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In myoblasts, decreased endogenous Foxc2 reduced cell proliferation activity, while increased expression of Foxc2 promoted cell proliferation [ 13 ]. In osteoblasts, upregulated Foxc2 facilitates cell proliferation in vitro [ 32 ], and Foxc2 might encourage the survival and proliferation of osteoblasts by upregulating integrin β 1 [ 11 ]. Consistent with the previous reports [ 13 , 32 ], our data showed that the proliferation of Foxc2 gene-transfected SCAP was slightly stronger than that of the other three groups.…”
Section: Discussionmentioning
confidence: 99%
“…In osteoblasts, upregulated Foxc2 facilitates cell proliferation in vitro [ 32 ], and Foxc2 might encourage the survival and proliferation of osteoblasts by upregulating integrin β 1 [ 11 ]. Consistent with the previous reports [ 13 , 32 ], our data showed that the proliferation of Foxc2 gene-transfected SCAP was slightly stronger than that of the other three groups. However, the proliferative activity of Foxc2 and BMP2 double gene-transfected SCAP was reduced on day 8, which implies that Foxc2 and BMP2 synergistically control the proliferation of SCAP.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, Wang et al used a qRT-PCR methodology (29). They reported that bone morphogenetic factor-7 played an essential role in cell hemostasis and in regulating the anabolism and catabolism of intervertebral discs.…”
Section: █ Discussionmentioning
confidence: 99%
“…BMP7 is a pleiotropic cytokine which transforms mesenchymal cells into bone and cartilage. Owing to its osteogenic activity, BMP7 has been approved by the FDA for the treatment of bone-related diseases, such as spinal fusion and bone fracture healing (36,37). BMP7 has also been implicated in tumors, such as prostate and breast cancer (38,39).…”
Section: Discussionmentioning
confidence: 99%